Ultra‑Broadband and Ultra-High Electromagnetic Interference Shielding Performance of Aligned and Compact MXene Films - Huang, Weiqiang; Liu, Xuebin; Wang, Yunfan; Feng, Jiyong; Huang, Junhua; Dai, Zhenxi; Yang, Shaodian; Pei, Songfeng; Zhong, Jing; Gui, Xuchun (Nano-Micro Letters, 2025)
With the rapid development of electronic detective techniques, there is an urgent need for broadband (from microwave to infrared) stealth of aerospace equipment. However, achieving effective broadband stealth primarily relies on the composite of multi-layer coatings of different materials, while realizing broadband stealth with a single material remains a significant challenge. Herein, we reported a highly compact MXene film with aligned nanosheets through a continuous centrifugal spraying strategy. The film exhibits an exceptional electromagnetic interference shielding effectiveness of 45 dB in gigahertz band (8.2–40 GHz) and 59 dB in terahertz band (0.2–1.6 THz) at a thickness of 2.25 μm, owing to the high conductivity (1.03 × 106 S m−1). Moreover, exceptionally high specific shielding effectiveness of 1.545 × 106 dB cm2 g⁻1 has been demonstrated by the film, which is the highest value reported for shielding films. Additionally, the film exhibits an ultra-low infrared emissivity of 0.1 in the wide-range infrared band (2.5–16.0 μm), indicating its excellent infrared stealth performance for day-/nighttime outdoor environments. Moreover, the film demonstrates efficient electrothermal performance, including a high saturated temperature (over 120 °C at 1.0 V), a high heating rate (4.4 °C s−1 at 1.0 V), and a stable and uniform heating distribution. Therefore, this work provides a promising strategy for protecting equipment from multispectral electromagnetic interference and inhibiting infrared detection. Highlights: 1 A highly aligned and compact MXene film for ultra‑broadband and ultra-high electromagnetic interference shielding was fabricated by continuous centrifugal spraying strategy. 2 The film exhibits an exceptional electromagnetic interference shielding effectiveness (EMI SE) of 45 dB, specific shielding effectiveness of 1.545 × 106 dB cm2 g⁻1 in gigahertz band (8.2–40 GHz), and EMI SE of 59 dB in terahertz band (0.2–1.6 THz). 3 The film exhibits an ultra-low infrared emissivity of 0.1 in the infrared band (2.5–16.0 μm) and an efficient electrothermal performance.